Charge disproportionation in the spin-liquid candidate κ-(ET)_{2}Cu_{2}(CN)_{3} at 6 K revealed by ^{63}Cu NQR measurements - T. Kobayashi; Q.-P. Ding; H. Taniguchi; K. Satoh; A. Kawamoto; Y. Furukawa (Physical Review Research, 2020)
The spin-liquid candidate κ-(ET)_{2}Cu_{2}(CN)_{3} [ET: bis(ethylenedithio)tetrathiafulvalene] does not exhibit magnetic ordering down to a very low temperature, but shows a mysterious anomaly at 6 K. The origin of the so-called 6-K anomaly is still under debate. We carried out nuclear quadrupole resonance (NQR) measurements on the copper sites of the insulating layers, which are sensitive to the charge dynamics unlike conventional spin-1/2 nuclear magnetic resonance (NMR). The main finding of this Rapid Communication is that the observation of a sharp peak behavior in the nuclear spin-lattice relaxation rate T_{1}^{−1} of ^{63}Cu NQR at 6 K while T_{1}^{−1} of both ^{13}C and ^{1}H NMR show no clear anomaly. This behavior can be understood as a second-order phase transition related to charge disproportionation in the ET layers.